Antifungal Mechanisms of a Chinese Herbal Medicine, Cao Huang Gui Xiang, Against Candida Species - Yue, Huizhen; Xu, Xiaolong; He, Shasha; Cui, Xuran; Guo, Yuhong; Zhao, Jingxia; Peng, Bing; Liu, Qingquan (Frontiers in Pharmacology, 2022)
Cao Huang Gui Xiang (CHGX) formula, a Chinese herbal medicine, has been empirically used for the treatment of Candida infections. In the present study, we discovered that the CHGX show potent antifungal activities against the major human fungal pathogen Candida albicans and other clinical Candida species. Besides, we indicated that CHGX had in vivo efficacy on treating C. albicans infection in mice without noticeable toxicity at the clinical therapeutic concentration. We then set out to investigate the antifungal mechanisms of CHGX against C. albicans. We found that that CHGX played an important role in inhibiting biofilm formation and filament development, two critical virulence factors of C. albicans. We further demonstrated that CHGX disrupts cell membrane integrity, triggers the accumulation of reactive oxygen species (ROS) and consumption of adenosine triphosphate (ATP), followed by a rapid fungal cell death in C. albicans. Multiple pathways, including the conserved Ras1-cAMP pathway and mitochondrial protein Mcu1 are involved in CHGX-induced cell death. Our finding expands the understanding of antifungal mechanism of CHGX against C. albicans, and provides new insights in treating patients with Candida infections in clinical practice.